Evaluation of semi-intensive green roofs with drainage layers made out of recycled and reused materials (2020)
Green roof systems represent an opportunity to mitigate the effect of natural soil loss due to the development of urban infrastructure, which significantly affects natural processes such as the hydrological water cycle. This technology also has the potential to reduce the indoor building temperature and increase the durability of waterproof membranes, reduce run-off water and heat island effects, create meeting places, and allow the development of biological species. However, despite the described benefits, the use of this technology is still limited due to the costs and the environmental impact from using non-renewable building materials. Therefore, this article presents the hydraulic and thermal analysis of different semi-intensive green roofs using recycled (rubber and high density polyethylene (HDPE) trays) and reused materials (polyethylene (PET) bottles) in their drainage layers. Then, three roof systems were evaluated and compared to traditional drainage systems made with natural stone aggregates. Results showed that some systems are more useful when the goal is to reduce temperature, while others are more effective for water retention. Additionally, this study presents evidence of the potential of reducing the dead loads and costs of green roofs by using recycled and reused materials in drainage systems.